Style momentum in Hong Kong, Korea and Singapore stock markets - Chen, Jasen Wen Jian (2009)
Employing momentum trading strategies is counter to conventional rational investment behaviour. Interestingly, style momentum strategies in particular, are gaining popularity because of its proven profitability in developed markets. In this report, the focus is on Asian stock markets, where we investigate the profitability of style momentum investment strategies for Singapore, Hong Kong and South Korea stock exchanges, using all listed stocks, excluding REITs, over the period of 1993-2007. Our results reveal that style momentum investment strategies do not yield significant momentum profits in the three emerging markets. There is also no indication of statistical significant differences between style and price portfolios. Future research may seek to investigate the other emerging markets and consider other factors such as economic variables, information diffusion and economic cycles.